The Effect of Maximum Daily Temperature on Outdoor Violence - Cruz, Erik (Crime & delinquency, 2023)
Although temperature aggression theory maintains that a high temperature engenders more aggressive behavior by irritating individuals, routine activity theory asserts that violent crime increases as temperature rises because of enhanced interaction among the public in outdoor settings. We investigate the effect of maximum daily temperature on whether crime victims are physically injured during the commission of an outdoor criminal offense in Cleveland, Ohio. We focus on violent crimes occurring outdoors because most U.S. households have central air-conditioning or room air conditioners. Two autoregressive integrative moving average (ARIMA) analyses provide support for routine activity theory because although maximum daily temperature has a strong positive effect on the frequency of violent crimes occurring outdoors, it has little influence on the physical injury of crime victims.